Effectiveness of Contemporary Da‘wah Strategies: An Empirical Review and Synthesis of Existing Literature - Bello Ali; Aminu Sa’ad Abdullahi; Muhammad Muhammad; Murjanatu Ismail Agwaru (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
Purpose– The rapid expansion of digital communication technologies has fundamentally transformed contemporary da‘wah, shifting Islamic outreach from conventional face-to-face preaching toward interactive digital platforms. This study examines the effectiveness of contemporary da‘wah strategies by synthesizing empirical evidence on the factors that influence successful digital Islamic communication and audience engagement across social media environments. Design/methodology/approach– This study employs a qualitative systematic literature review (SLR) methodology. Empirical studies published between 2017 and 2026 were systematically identified, screened, and analyzed using thematic content analysis. The review synthesizes evidence concerning digital da‘wah practices across major social media platforms, with particular attention to communication strategies, audience engagement, technological affordances, and the emerging role of social media handlers. Findings– The review demonstrates that digital platforms—including Facebook, WhatsApp, YouTube, Instagram, TikTok, Telegram, and X—have substantially expanded the reach of Islamic knowledge, strengthened audience participation, and facilitated the formation of virtual religious communities. The effectiveness of contemporary da‘wah is determined by the interaction of several key factors: content quality, preacher credibility, communication competence, digital literacy, audience-centred messaging, platform suitability, and the strategic functions of social media handlers in content production, moderation, audience engagement, and platform management. Nevertheless, challenges such as misinformation, concerns regarding content authenticity, unequal digital access, and limited technological competence continue to constrain online da‘wah effectiveness. Research implications/limitations– As a literature-based study, the findings rely on existing empirical evidence and do not assess the effectiveness of specific digital da‘wah programs. Future research should employ comparative and mixed-methods designs to evaluate digital da‘wah strategies across different cultural, institutional, and technological contexts. Originality/value– This study contributes to contemporary Islamic communication scholarship by providing an integrative synthesis of empirical research on digital da‘wah. It develops a comprehensive framework demonstrating that effective contemporary da‘wah depends on the integration of authentic Islamic principles, strategic communication, technological innovation, digital literacy, and professional social media management, thereby offering practical guidance for scholars, Islamic organizations, and digital content practitioners.